Effectiveness of dialectical behavior therapy (DBT) in reducing suicidal behaviors and improving emotion regulation among adolescents: A systematic review - Pratiwi Tangkawarow; Yossie Susanti Eka Putri; Achir Yani S Hamid; Ria Utami Panjaitan (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Suicidal behavior and non-suicidal self-injury (NSSI) among adolescents are increasing globally, and the WHO ranks suicide as the third leading cause of death among adolescents. In Indonesia, the 2022 I-NAMH Survey shows that 14.4% of adolescents have suicidal thoughts and 4.7% have attempted suicide. This situation highlights the importance of interventions that can improve emotional regulation and reduce self-harming behavior. Dialectical Behavior Therapy for Adolescents (DBT-A) has shown potential, but its effectiveness among adolescents remains inconsistent. Purpose: To evaluate the effectiveness of DBT-A in reducing suicidal behaviors and NSSI and improving emotional regulation in adolescents. Method: A literature search was conducted via PubMed and ScienceDirect for publications from 2011 to 2025. Inclusion criteria included quantitative studies with DBT interventions in adolescents aged 12–19 years, with outcomes of suicidal ideation, self-harm, or emotional regulation. Of the 585 articles identified, 10 studies met the criteria and were assessed for quality using the Joanna Briggs Institute (JBI) instrument. Results: DBT-A consistently reduces self-harm behavior, NSSI, and suicidal ideation. Most studies report significant improvements in emotional regulation, with the highest effectiveness seen in multi-component programs involving families. Studies with shorter durations or limited components show less stable results. Conclusion: DBT is effective in reducing self-harm and suicidal ideation and improving emotional regulation. Structured implementation of DBT involving families, including cultural adaptation and the use of digital platforms, has the potential to expand access to services. Further research is needed to test the long-term effectiveness and application of DBT in more diverse adolescent populations.